Is the distribution of care quality provided under pay-for-performance equitable? Evidence from the Advancing Quality programme in England. Issue 1 (December 2016) - Mason, Thomas; Lau, Yiu-Shing; Sutton, Matthew
Abstract Background The limited number of existing previous studies of the distribution of quality under NHS Pay-for-performance (P4P) by income deprivation have not analysed the relationship at the individual level and have been restricted to assessing P4P in the primary care setting. In this study, we set out to examine how achievement of P4P 'quality measures' for which NHS hospitals were paid was distributed by income deprivation. Methods Design : Retrospective analysis of performance data reported by hospitals, examining how the probability of receiving 23 indicators varied by patients' area deprivation using logistic regression controlling for age and gender.Sample : We use anonymised observational data on 73, 002 patients admitted to hospitals in the North West of England between October 2008 and March 2010 for the following five reasons: acute myocardial infarction; coronary artery bypass grafting; heart failure; hip and knee replacement; and pneumonia. Results The relationship between quality and deprivation varies depending on the point of delivery in the treatment pathway, and on whether delivered for conditions in scheduled or unscheduled care. For diagnostic tests on arrival, receipt of quality was: pro-rich in scheduled care and pro-poor in unscheduled care. Receipt of quality was pro-poor for pre-surgery measures in scheduled care. Receipt of quality at discharge was pro-rich. Conclusion Unlike in primary care, in secondary care quality is not systemically distributed by income deprivation under P4P. Whilst improvements in health inequalities are important system objectives; they may not necessarily be achieved by the adoption of P4P schemes in hospitals.